Existing Hypotheses about the Emergence of Nonsense Syllables in the Chant Tradition of Teretismata and Kratēmata in Byzantine Music - Varelas, Vassileios (Journal of the International Society for Orthodox Music, 2023)
In the present essay, I review and evaluate the three main hypotheses about the historical background and emergence of the nonsense syllables in the chant tradition of teretismata and kratēmata in Byzantine music. The different historical hypotheses as to the historical roots and development of this singing practice are examined and analyzed thoroughly, namely those of Gregorios Stathis (1979, 2014), Diane Touliatos (1989), and Grigorios Anastasiou (2005). The aim of the analysis is to summarise and discuss the contribution of the up-to-date historical hypotheses to the theoretical approaches of the topic, including the identification of potential flaws, lacunae and inadequacies of their explanatory power. Touliatos takes antiquity as a starting point for her hypothesis and posits the roots of nonsense syllables in the music of Ancient Greece. After a historical gap of several centuries, those syllables reappear in the Byzantine music during the 14th c. Stathis and Anastasiou examine the phenomenon exclusively within the boundaries of Byzantine music. Before reviewing the three hypotheses concerning the historical development of nonsense syllables in Byzantine music, we must consider the sources on which the theories are postulated.